2013
DOI: 10.1039/c3an01113e
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of microfluidic PET tracer synthesis with Cerenkov imaging

Abstract: Microfluidic technologies provide an attractive platform for the synthesis of radiolabeled compounds. Visualization of radioisotopes on chip is critical for synthesis optimization and technological development. With Cerenkov imaging, beta particle emitting isotopes can be localized with a sensitive CCD camera. In order for Cerenkov imaging to also serve as a quantitative tool, it is necessary to understand how material properties relevant to Cerenkov emission, namely, index of refraction and beta particle stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…We have shown that initial in vitro phantom studies produced results comparable to those previously reported by other groups (46, 10–12, 15, 2932). Increases in measured radiance positively correlated with increases in the quantity of activity irrespective of the radionuclide measured ( 90 Y or 177 Lu; Fig.…”
Section: Discussionsupporting
confidence: 87%
“…We have shown that initial in vitro phantom studies produced results comparable to those previously reported by other groups (46, 10–12, 15, 2932). Increases in measured radiance positively correlated with increases in the quantity of activity irrespective of the radionuclide measured ( 90 Y or 177 Lu; Fig.…”
Section: Discussionsupporting
confidence: 87%
“…For radio-thin-layer chromatography (TLC) analysis, TLC plates (Baker-flex silica gel IB-F sheets 2.5 × 7.5 cm, J.T. Baker, Phillipsburg, NJ) were spotted with 1 μL samples of the crude intermediate, crude final product, or purified final product, and were developed in 80% v/v MeCN in H 2 O, and then scanned with a radio-TLC scanner (miniGita star, Raytest, Inc., Wilmington, NC, USA), or with a Cerenkov luminescence imaging system (Dooraghi et al 2013). Retention factors of the observed radioactive species were: 0.0 ([ 18 F]fluoride), 0.3 ([ 18 F]FET), and 0.8 (fluorinated intermediate).…”
Section: Methodsmentioning
confidence: 99%
“…Of the several different microfluidic approaches reported in the last decade (Elizarov 2009;Keng and van Dam 2015;Miller et al 2010;Pascali and Matesic 2016;Rensch et al 2013), microvolume reaction approaches offer the greatest potential for reagent and instrument reductions (Dooraghi et al 2013;Elizarov et al 2010;Iwata et al 2018;Keng et al 2016;Lebedev et al 2012;Wang et al 2017). A particular configuration we are exploring is performing reactions in microliter-sized droplets on simple Teflon-coated silicon microfluidic chips, which has advantages of simple operation, low-cost disposable chips, and a compact system size, which reduces the necessary shielding.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of decay-products enables quantifi cation of radioisotopes and is useful in a variety of cellular assays or monitoring microfl uidic devices that process radioisotopes. Detecting Cerenkov emissions with a sensitive CCD camera, Dooraghi et al 93 (Fig. 11e,f).…”
Section: Cerenkov Imagingmentioning
confidence: 99%
“…However, ITO is expensive, and oft en requires an additional layer of metal for the traces and contact pads, due to its relatively high resistivity. Hu et al demonstrated that single-walled carbon nanotubes can be used as a somewhat cheaper, transparent alternative to ITO 93 . To simplify fabrication, a recent report has shown that it is possible to introduce "windows" into actuation electrodes made of opaque electrode materials such as metals 95 , enabling optical detection of droplets without transparent conductors.…”
Section: Cerenkov Imagingmentioning
confidence: 99%